Antitumor activity and safety of camrelizumab combined with apatinib in patients with relapsed or refractory peripheral T-cell lymphoma: An open-label, multicenter, phase II study - Liu, Yanfei; Song, Yuqin; Zuo, Shubo; Zhang, Xian; Liu, Hui; Wang, Jingwen; Wang, Jingbo; Tang, Yongjing; Zheng, Wen; Ying, Zhitao; Ping, Lingyan; Zhang, Chen; et al. (Frontiers in Immunology, 2023)
Introduction The treatment for relapsed/refractory peripheral T-cell lymphoma (r/r PTCL) is suboptimal. This open-label, multicenter, single-arm study aimed to investigate the antitumor activity and safety of camrelizumab (a PD-1 blockade) plus apatinib (an antiangiogenic agent) for patients with r/r PTCL. Methods Eligible patients with r/r PTCL were enrolled and received camrelizumab 200 mg intravenously every 2 weeks and apatinib 500 or 250 mg orally once daily, 4 weeks as a cycle. The primary endpoint was overall response rate (ORR). Results A total of 20 patients were enrolled and received study medications in the study, with a median number of prior treatment line of 3 (range 1-6). At the cutoff date of March 4, 2022, the median follow-up was 27.2 months (range: 0.5-39.9), and three patients remained on treatment. Six patients had early discontinuation without tumor response evaluation. For all patients, the ORR was 30% (6/20) (95% confidence interval [CI], 11.9% to 54.3%), with two patients (10%) achieving complete response. The median progression-free survival (PFS) and median overall survival for all patients were 5.6 months (95% CI, 1.8 to not reached) and 16.7 months (95% CI, 2.8 to not reached), respectively. Patients with PD-L1 expression ≥50% (3 patients) had a numerically higher ORR and longer median PFS than those with PD-L1 expression < 50% (5 patients). The most commonly reported grade 3 or higher adverse events were hyperlipidemia (15%), hypokalemia (15%) and anemia (15%). No treatment-related deaths occurred. Discussion In this study, PD-1 inhibitors plus low-dose antiangiogenic drugs presented preliminary antitumor activity and manageable toxicity in patients with r/r PTCL.